Good Riddance to Big Insurance Mergers - Dafny, Leemore S (The New England journal of medicine, 2017)
Federal judges have issued preliminary injunctions halting mergers of four of the five largest U.S. health insurers. These decisions provide more precedent to support challenges of mergers between competitors in health care markets — whether payers or providers. Eighteen months after four of the five largest U.S. health insurers announced multibillion-dollar merger deals, federal judges, siding with the Department of Justice (DOJ), have issued preliminary injunctions halting the two transactions. These decisions will cost the insurers: they spent over $2 billion trying to get the deals done, and the would-be acquirers are due to pay $2.85 billion in breakup fees — and possibly billions more in damages. 1 – 3 Moreover, the parties’ conduct has further damaged the public’s view of the insurance industry. Having suffered similar defeats at the hands of the Federal Trade Commission (FTC), hospitals are enjoying . . .